Entre « traces » et jugements moraux : des « matérialités » qui forgent les corps, les crimes et les victimes - Larissa Nadai; Cilmara Veiga (Brésil(s), 2019)
In this article, we seek to contrast two distinct empirical fields. On one hand, Larissa Nadai presents the links between legal-medicine classes and technical bibliographies of forensic sexology and forensics reports on rape crimes forged by the Medico-Legal Institute of Campinas, São Paulo, between 2004 and 2005. On the other hand, Cilmara Veiga examines newspapers articles and official documents that composed the criminal processes produced from the series of five crimes that shocked the city of Juiz de Fora, in the state of Minas Gerais, in the 1990s. Our intention in placing these different ethnographic materials in dialogue resulted from a belief that sexual violence and its definition as a rape crime are a privileged locus to consider materialities and state procedures. By showing how the very notion of materiality is a powerful technical, scientific, and bureaucratic artifice, we seek to unveil gendered mechanisms by which bodies, crimes and criminals are governed.